The benefits of exercise for patients with haemophilia and recommendations for safe and effective physical activity. (28th March 2013) - Negrier, C.; Seuser, A.; Forsyth, A.; Lobet, S.; Llinas, A.; Rosas, M.; Heijnen, L.
Summary Most health care professionals involved in the management of people with haemophilia (PWH) believe that exercise is beneficial and its practice is widely encouraged. This article aims to demonstrate that appropriate exercise (adapted to the special needs of the individual PWH) may be beneficial for all PWH through improved physical, psychosocial and medical status. Based on evidence gathered from the literature, many PWH, particularly those using long‐term prophylaxis or exhibiting a mild/moderate bleeding phenotype, are as active as their healthy peers. PWH experience the same benefits of exercise as the general population, being physically healthier than if sedentary and enjoying a higher quality of life (QoL) through social inclusion and higher self‐esteem. PWH can also gain physically from increased muscle strength, joint health, balance and flexibility achieved through physiotherapy, physical activity, exercise and sport. Conversely, very little data exist on activity levels of PWH in countries with limited resources. However, regarding specific exercise recommendations in PWH, there is a lack of randomized clinical trials, and consequently formal, evidence‐based guidelines have not been produced. Based on published evidence from this review of the literature, together with the clinical experience of the authors, a series of recommendations for the safe participation of PWH in regular physical activities, exercises and sport are now proposed. In summary, we believe that appropriately modified programmes can potentially allow all PWH to experience the physical and psychosocial benefits of being physically active which may ultimately lead to an improved QoL.